Health Acceptance through Camp: Mixed-Method Data from a Central-European Therapeutic Recreational Based Camp for Seriously Ill Children - Papp, Zsuzsanna Katalin; Somogyi, Borbála; Wilson, Cait; Török, Szabolcs (European Journal of Mental Health, 2021)
This study aims to understand how youth living with serious illness retrospectively value their therapeutic recreational (TR) based camp experience. We focus primarily on how they learned to accept their health condition, what they consider the most valuable outcome from camp, and through which mechanisms the camp contributed to these outcomes. The study applied a mixed-method online survey measuring learning outcomes retrospectively in a sample of 18–25-year-old camp alumni (N = 60) from the Hungarian ‘Camp of Courage’ (Bátor Tábor). Questions regarding illness acceptance and health competence formed the quantitative part and were analyzed via descriptive statistics. We assessed the most important camp outcomes with open-ended survey questions in the qualitative part, and applied a deductive thematic analysis method. Our research found that illness acceptance and health competence are important constructs for young adults, and TR-based camps may play a major role in their development. We organized recurring themes under the overarching theme ‘restorative experience and growth’ as the main benefit from camp and under ‘unconditional acceptance’ as the camp mechanism contributing to this benefit. Those campers who have experienced illness-based limitations in life before expressed most benefits in psychosocial domains. They highlighted the acceptance, empathy, and social support at camp, experienced mainly through interactions with peers and camp counselors. We may conclude that Camp of Courage provides a suitable environment for psychosocial rehabilitation of youth affected by childhood cancer or other serious illness. We recommend further research on the rolesof illness acceptance and social interactions at camp.